Case reportEosinophilic cellulitis (Wells’ syndrome) caused by a temporary henna tattoo - Nacaroglu, Hikmet Tekin; Celegen, Mehmet; Karkıner, Canan Sule Unsal; Günay, Ilker; Diniz, Gulden; Can, Demet (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Eosinophilic cellulitis (Wells’ syndrome) is an uncommon condition of unknown etiology. Wells’ syndrome is usually seen in adulthood but very rare in childhood. Although pathogenesis of the disease is not very clear, it is a hypersensitivity reaction developing against a variety of exogenous and endogenous antigenic stimuli. Paraphenylenediamine is a strong allergen frequently used as a temporary henna tattoo, which makes the color darker. Here, a 9-year-old male patient with Wells’ syndrome is presented, which developed following a temporary henna tattoo and shown by the patch test sensitivity to paraphenylenediamine.